PERCEPCIÓN Y ACTITUDES SOBRE LA PROBLEMÁTICA DEL ABORTO PROVOCADO EN ESTUDIANTES DE MEDICINA DE ARGENTINA Y CHILE. UN ESTUDIO DESCRIPTIVO - Pardo Carvallo, Cardeu Jesús (2026)
Introduction. Induced abortion is a clinical, ethical, and public health issue. Medical students’ attitudes are relevantbecause they may influence future care and the implementation of sexual and reproductive health policies. Objectives.To identify perceptions and attitudes toward induced abortion among medical students from the UniversidadNacional de La Plata, the Universidad de Buenos Aires and the Universidad de Chile. Methods. An observational,descriptive, cross-sectional study with a mixed-methods component was conducted through an online survey administeredbetween May and July 2024. A total of 743 medical students from the third year onward, enrolled in threepublic universities, were included. Sociodemographic variables, legal and clinical knowledge, conscientious objection,training received, attitudes, and willingness to participate in a legal abortion were assessed. Descriptive and comparativeanalyses were performed using Stata. Results. Most participants were female (68.0%), and 51.0% were in thethird year of study. Overall, 75.0% supported abortion whenever the woman consented, and 22.0% supported it onlyunder special circumstances; 73.0% would participate in a legal abortion. Legal regulation was known by 66.0% ofparticipants, and 78.0% were familiar with the concept of conscientious objection. In addition, 74.0% considered thatthe legislation is only partially implemented. Training was rated as insufficient by 45.0%, and knowledge of surgicalprotocols was limited. Among those unwilling to participate, personal or conscientious reasons (57.2%) and lack ofpreparation or knowledge (47.8%) were the main reasons. Conclusion. Favorable attitudes toward induced abortionand a high willingness to participate in legal abortions predominated; however, personal and educational barriers maylimit participation in clinical practice.